2020
DOI: 10.31234/osf.io/q4k5b
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of anxiety and depression in South Asia during COVID-19: A systematic review and meta-analysis

Abstract: Introduction: The COVID-19 pandemic has impacted biopsychosocial health and wellbeing globally. Pre-pandemic studies suggest a high prevalence of common mental disorders, including anxiety and depression in South Asian countries, which may aggravate during this pandemic. This systematic meta-analytic review was conducted to estimate the pooled prevalence of anxiety and depression in South Asian countries during the COVID-19 pandemic. Method: We systematically searched for cross-sectional studies on eight major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 84 publications
1
12
0
Order By: Relevance
“…Applying some of the mandatory restrictions, including social distancing at the earlier period of the pandemic inception, people started grabbing and worrying about their lives and personal safety, fear of getting infected, lost a beloved one, absence of appropriate treatment, etc., which influenced the risk of depression, anxiety, and stress (Hossain et al, 2020a(Hossain et al, , 2020b. Thus, participants belonging to general people and students cohorts had to experience mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Applying some of the mandatory restrictions, including social distancing at the earlier period of the pandemic inception, people started grabbing and worrying about their lives and personal safety, fear of getting infected, lost a beloved one, absence of appropriate treatment, etc., which influenced the risk of depression, anxiety, and stress (Hossain et al, 2020a(Hossain et al, , 2020b. Thus, participants belonging to general people and students cohorts had to experience mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…However, these measures led to restricted movements and decreased social interactions with others, which may be extremely burdensome in some of the people. Such isolation and lack of social interaction influence people psychologically and emotionally, leading to a higher level of loneliness, anxiety, fear, stress, depression, tediousness, and so forth (Hossain et al, 2020; Islam et al, 2020; Pedrosa et al, 2020). As a result of unstable mental health, circumstances may easily lead the individual to suicidality increases, especially among teenagers (Mamun et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The Coronavirus Disease 2019 , since its start and following massive global transmission spread has shaped several challenges for the healthcare workers and the general people across the world (Jahan et al, 2021;Mamun, Bodrud-Doza, et al, 2020). The pandemic is expected to lead to a substantial degree of mental health crisis along with other aspects of the quality of life (Hossain et al, 2020;Khan et al, 2020;Pedrosa et al, 2020). Hence, the World Health Organization (2020) has issued brief messages related to psychological and mental health considerations and has emphasized the execution of psychological first aid.…”
Section: Introductionmentioning
confidence: 99%
“…The pooled prevalence rate for depression in African population (45%) is significantly higher than those in China reported Bareeqa et p-value <0.0001) [12][13][14][15] . The pooled prevalence rate for depression in the African population (45%) is higher than those in Spain (23%; p-value <0.0001) 50 and in South Asian countries reported by Hossain et al (2020) (34%; p-value <0.0001) 51 . The pooled prevalence for depression in Africa (45%) is also higher than the pooled prevalence in a study which had over 17 countries reported by Luo et al (28%; p-value <0.0001) 52 and higher than another study of 10 countries reported by Salari et al (34%; p-value <0.0001) 18 , however, the prevalence rate for depression in Africa is lower than Italythe country with the highest prevalence for depression (67%) 52 .…”
Section: Comparisons Of Results With Prior Meta-analysismentioning
confidence: 68%
“…The pooled prevalence rate for anxiety in African population is 37%, which is significantly higher than those in China reported in Bareeqa [12][13][14][15] , and those in Spain (20%; p-value <0.0001) 50 . However, notably, the pooled prevalence rate for anxiety in South Asian countries is significantly higher than that in Africa (41.3%; p-value <0.0001) 51 . In addition, the pooled prevalence of anxiety in Africa (37%) is higher than those in individual cross-country individual studies, such as a study of 10 countries (China, India, Japan, Iran, Iraq, Italy, Nepal, Nigeria, Spain, and the UK) (32%; pvalue <0.0001) 18 and a study in 17 countries in the regions of Asia (China, India, Japan, Pakistan, Singapore, Vietnam), Middle East (Iran, Israel), Europe (Denmark, Greece, Italy, Spain, Turkey), and Latin America (Argentina, Brazil, Chile, and Mexico) (33%; p-value <0.0001) 52 .…”
Section: Comparisons Of Results With Prior Meta-analysismentioning
confidence: 87%